The interface of timber and non-timber resources: declining resources for subsistance livelihoods - a southern case study from Brazilian Amazonia - Shanley, P.; Luz, L.; Cymerys, M. (Routledge, 2002)
Given the importance of non-timber forest resources to subsistence livelihoods, the increased rate of logging in Amazonia, and the pronounced overlap of timber and non-timber species, it is important to evaluate the altered composition and abundance of NTFPs. In this changing landscape, it is vital to understand which species are widely utilized for their non-timber value, which NTFPs species are extracted for timber and what their comparative timber and non-timber value is. To answer these questions, quantitative and qualitative results of a seven-year study are provided on the use of plant and animal forest resources by 30 households residing in an area of terra firme (upland dry) forest undergoing selective logging.